2021
DOI: 10.1177/1557085120987628
|View full text |Cite
|
Sign up to set email alerts
|

The Cycle of Violence: Abused and Neglected Girls to Adult Female Offenders

Abstract: Drawing on findings from a prospective cohort design study that followed abused and neglected children and demographically matched controls into adulthood, this paper focuses on these abused and neglected girls and one important consequence—the extent to which these victims become offenders themselves. We ask four questions: Is criminal behavior among abused and neglected girls and women rare? Are abused and neglected girls at increased risk for becoming violent offenders? Does childhood maltreatment affect cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…African American women with children experiencing homelessness could benefit from similarly-situated transitional living centers like Nia Imani in other U.S. urban metropolitan areas, where varying forms of violence are acknowledged in the healing process, and where all components of Figure 1 are evaluated and addressed. Similarly it is important to note that throughout our analyses, the "cycle of violence" was identified and was central to women's explication of their experiences; however, newer violence literature suggests referencing a cyclical process of violence may be harmful or stigmatizing when used out of context (Thornberry et al, 2012;Widom & Osborn, 2021). Women's experiences indicated that violence is a result of circumstance, influenced by factors of a structural and oppressive nature, including structural racism, sexism, and poverty as illustrated in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…African American women with children experiencing homelessness could benefit from similarly-situated transitional living centers like Nia Imani in other U.S. urban metropolitan areas, where varying forms of violence are acknowledged in the healing process, and where all components of Figure 1 are evaluated and addressed. Similarly it is important to note that throughout our analyses, the "cycle of violence" was identified and was central to women's explication of their experiences; however, newer violence literature suggests referencing a cyclical process of violence may be harmful or stigmatizing when used out of context (Thornberry et al, 2012;Widom & Osborn, 2021). Women's experiences indicated that violence is a result of circumstance, influenced by factors of a structural and oppressive nature, including structural racism, sexism, and poverty as illustrated in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that incarcerated female juvenile and adult offenders have reported experiencing neglect in childhood, intimate partner violence, and verbal, physical, and sexual abuse (Belknap & Holsinger, 2006;Jones et al, 2018;Lynch et al, 2012;Severson et al, 2009;Tripodi & Pettus-Davis, 2013). The experiences of these traumas not only increase females' chances for engaging in delinquent and criminal behavior, but they will often result in females using drugs and alcohol as a coping mechanism (Bailey & McCloskey, 2005;Belknap, 2007;Boyd, 1993;Chen et al 2004;Chesney-Lind & Pasko, 2004;Comack, 2005;Gilfus, 1992;Goodkind et al, 2006;Kilpatrick et al, 2000;Luster & Small, 1997;Miller & Downs, 1993;Saunders et al, 1999;Widom, 1995;Widom & Osborn, 2021). While drug and alcohol use may be a result of an attempt to cope with early trauma, researchers have not explored the possibility that psychopathic personality traits may serve as a protective factor for coping with trauma.…”
Section: Gender and Traumamentioning
confidence: 99%
“…For example, program developers could focus on a number of the factors that we identified as associated with abuse and mutual abuse which are potentially malleable (e.g., conflict management strategies as well as managing/controlling certain emotions). Such research and associated prevention programming could not only prove pivotal in addressing abuse in early adolescence but also prove to be protective for these same individuals later in life (Widom & Osborn, 2021).…”
Section: Implications and Conclusionmentioning
confidence: 99%